МАРГАНЕЦ ОЛИЙ СИЛИЦИДИ АСОСИДА САМАРАДОРЛИГИ ЮҚОРИ ТЕРМОБАТАРЕЯЛАРНИ ЯРАТИШ ИМКОНИЯТЛАРИ - Зикриллаев, Н.Ф.; Шоабдурахимова, М.М.; Уракова, Ф.Э.; Хусанов, А.; Қурбоналиев, Қ.Қ. (SCIENCE and SOCIETY, 2022)
On the basis of research on parameters of the higher manganese layer silicide it was established that current carriers in the formed manganese silicide are holes and their concentration is equal to , mobility of wound , which corresponds to the parameters and characteristics of existing thermal batteries, as well as determined by the value of its thermal coefficient of EMF is in the range of α=290÷360 μV/K.